Analyzing climate and energy policy integration: the case of the Mexican energy transition - Heiner von Lüpke; Mareike Well (Climate Policy, 2020)
One of the main challenges faced by climate policy makers today is to design and implement policies capable of transferring climate policy goals into sectoral actions towards transformational pathways. Hence, climate policies need to be of cross-cutting character, lead to coherence with sectoral goals and reconcile diverging sectoral interests. Against this background, Mexico has undertaken significant efforts to reform its energy sector, including goals for clean energy and energy efficiency, and the adoption of implementation mechanisms via the Law for Energy Transition of 2015. Furthermore, Mexico has introduced a complex climate governance system, including ambitious mitigation goals. In this paper, we applied concepts of climate policy integration to analyse whether integration between the policy subsystems of energy and climate change occurred in Mexico in terms of political discourse and negotiation, policy goals and instruments, and implementation; as well as the factors at work that lead to climate policy integration. We find that on the level of political discourse and negotiation, an integration process between the energy and climate subsystems occurred, influenced by the availability and market maturity of clean energy, mitigation scenarios and external events, such as the 2015 Paris Climate Change Conference. However, a combination of decisions on integrated climate-energy policy outputs, and preparing the public administration system for the implementation of integrated policies, is needed to enable appropriate institutional mandates, budgets and instruments and avoid institutional fragmentation. Omitting to take these decisions was identified as a major shortcoming in the political-administrative system, preventing higher levels of climate policy integration. Key policy insights The Mexican Energy Transition Law shows that policy windows can be used by policy makers to attain integrated energy-climate policy outputs and to advance national mitigation and energy sector goals. In order to make full use of integrated policy decisions, the administrative system has to follow suit by also introducing mandates, budgets and policy instruments of an integrative character. Climate policy integration in practice implies identifying and using the full potential of policy windows in order to ensure the raising of ambition under the Paris Agreement as well as achievement of sectoral policy objectives.
Keywords: 330; Developing countries; domestic policy instruments; energy policy; policy interactions/integration